COMPLIANCE ANALYSIS OF HEALTH PROTOCOL IMPLEMENTATION OF COVID-19 PREVENTION IN RESTAURANT SERVICES IN CONSUMER PROTECTION LEGAL PERSPECTIVE (Study Hotel Mataram City) - Herlina Herlina (International Journal of Social Science, 2022)
With the existence of covid 19 the Ministry of Tourism and Creative Economy responded quickly to this by issuing implementation guidelines in implementing the health protocol called Cleanliness, Health, Safety and Environmental Sustainability (CHSE) in the tourism sector, one of which is hotels and restaurants/eateries, As an effort to prevent the spread of Covid- 19, this is expected to protect business actors, especially consumers from the dangers of Covid-19 because it protects safety, security and comfort. The readiness of tourist attractions in receiving visitors must also receive special attention. Increasing awareness of the importance of implementing the CHSE protocol must be continuously fostered, so as to minimize the occurrence of negligence and can have a positive impact on each participant's environment. Restaurants are places that are prone to the spread of the Covid-19 virus. The purpose of this study was to determine and analyze the level of adherence to the implementation of health protocols and factors that have the potential to spread Covid-19 in restaurant services in the city of Mataram. Data collection techniques used in research are: observation, interviews, and documentation. The data analysis technique used is descriptive analysis. The results of this study are that compliance in implementing the Covid-19 prevention health protocol is influenced by 3 things, namely sanctions, establishing good relationships and knowing the purpose and function of these rules. Obstacles in the implementation of the Covid-19 prevention health protocol are, more than consumers themselves, because in changing people's behavior patterns to be able to carry out activities according to applicable regulations it is difficult to do, it requires a strong commitment from both the government in issuing policies, as well as those who apply the rules them (business actors)